2020
DOI: 10.1103/physrevd.101.012011
|View full text |Cite
|
Sign up to set email alerts
|

Resonances in e+e annihilation near 2.2 GeV

Abstract: Using the initial-state radiation method, the e + e − → KSKL cross section from 1.98 to 2.54 GeV is measured in a data sample of 469 fb −1 collected with the BABAR detector. The results are used in conjunction with previous BABAR results for the e + e − → K + K − , e + e − → π + π − , e + e − → π + π − η, and e + e − → ωππ cross sections to investigate the nature of the resonance structure recently observed by the BESIII experiment in the e + e − → K + K − cross section.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In the fitting process, we found that ρð2150Þ play dominant role to reproduce the line shape of e þ e − → π þ π − around 2.2 GeV [4]. We can find two solutions (solution A and solution B), both of which can reproduce the BABAR's data well.…”
Section: Numerical Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…In the fitting process, we found that ρð2150Þ play dominant role to reproduce the line shape of e þ e − → π þ π − around 2.2 GeV [4]. We can find two solutions (solution A and solution B), both of which can reproduce the BABAR's data well.…”
Section: Numerical Resultsmentioning
confidence: 73%
“…In the following, we will fit the cross section for e þ e − → π þ π − measured by the BABAR Collaboration [4], where an event accumulation near 2.2 GeV exists in the π þ π − invariant mass spectrum. As seen in Table II, π þ π − is the most dominant decay channel for the S-wave ρ mesons but not important to the D-wave ρ mesons, which is from the theoretical calculation in Ref.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations